Localização de descargas parciais nos enrolamentos de transformadores por meio da análise de pulsos de corrente - Arismar Morais Gonçalves Júnior (2018)
The early identification and location of high-frequency current pulses related to Partial Discharges ( ) in the solid insulation system of Power Transformers enables the optimization and planning of maintenance interventions, preventing unexpected power interruptions and reducing downtime. Even though several techniques for signal experimental generation and location have been proposed in the literature, limitations can still be noted, such as the difficulties in generating current signals similar to the in incipient conditions of the insulation degradation and in the appropriate location of these discharges. In view of these, in this work, new methods of experimental high-frequency current pulses generation and location are proposed, based on, respectively, the realization of small capacitive disturbances along taps of the transformer windings and in the use of Multiple Linear Regression models (). The proposed strategies allow the generation of current pulses similar to the resulting from the initial degradation of the transformers solid insulation and their effective location along the windings, even if only computational simulated data are employed in the adjustment of the locator linear regression models. In addition, case studies indicate that the localization strategy can be applied to the location of for both layer-type and disk-type winding configurations.